No Quick Fixes: Integrating Population Health Education and Quality Improvement in a Large Residency Program. Issue 5 (September 2022) - Shoup, John Paul; Kim, Azalea; Wilson, Jonathan; Pendergast, Jane; Ranard, Benjamin L.; Boggan, Joel C.
ABSTRACT: The intersection of population health (PH), quality improvement (QI), and health disparities is increasingly a focus in graduate medical education. However, it remains unclear how trainees may best improve disparities within clinical training environments. We integrated PH education for residents participating in a practical QI experience in a continuity clinic serving an underserved population. We analyzed whether PH education increased confidence in creating care plans and implementing team-based care strategies after selection of one of three QI metrics with known health disparities led to improvement. Posteducational session, attendees had odds of confidence in creating care plans 10.0 (95% confidence interval [CI] 4.6–21.7) times the presession period, whereas nonattendees' confidence was unchanged (OR 1.63, 95% CI 0.78–3.4). Residents participating in the QI project did not have higher confidence in creating a care plan at baseline (20% vs. 9.6%, p = .09) nor any additional shift in confidence versus other residents ( p = .57). There were no differences in QI metric performance rate trends for residents choosing a specific QI metric versus those that did not ( p > .33 for all comparisons). PH didactics can increase resident confidence around PH topics. However, translating such learning into outcomes and improved health equity may require dedicated efforts across residency training.